Casebook for DSM-5 diagnosis and treatment planning - Ventura, Elizabeth editor (Springer Publishing Company, 2017)
This unique casebook for graduate-level programs in the mental health professions is a masterful vehicle for students to put the new DSM-5 into practice by presenting actual clinical experiences from practitioners. It is distinguished from other casebooks by its presentation of real-life cases along with the rationale behind diagnostic criteria and a connection of DSM-5 criteria with symptomatology for each case. In addition, the detailed vignettes include a complete discussion of treatment interventions and client management that is crucial for students in helping professions. These treatment considerations are inclusive of a wide range of evidence-based approaches. Multiple cases are presented within each major category of disorders to help students understand the nature of differential diagnosis. Cases also reflect cultural and social consideration in making diagnostic decisions. Each case is consistently formatted to include an overview of the client, symptoms/problems, diagnosis, and treatment interventions, including components, applications, and results/prognosis. Readers will have an opportunity to formulate their own reactions and diagnostic impressions for each case before the commentary reveals the correct conclusion. An ideal text to enhance courses in psychopathology and diagnosis, as well as practicum and internship, the casebook will diversify and broaden the classroom experience by enlightening students with compelling clinical cases that have been experienced by practicing professionals. --